Urban–rural differences in the socioeconomic deprivation–Sexual behavior link in Kenya - Dodoo, F. Nii-Amoo; Zulu, Eliya M.; Ezeh, Alex C. (Social science & medicine (1982), 2007)
We compare the impact of socioeconomic deprivation on risky sexual outcomes in rural and urban Kenya. Quantitative data are drawn from the Demographic & Health Surveys (DHS) and qualitative data from the Sexual Networking and Associated Reproductive and Social Health Concerns study. Using two separate indicators of deprivation we show that, although poverty is significantly associated with the examined sexual outcomes in all settings, the urban poor are significantly more likely than their rural counterparts to have an early sexual debut and a greater incidence of multiple sexual partnerships. The disadvantage of the urban poor is accentuated for married women; those in Nairobi's slums are at least three times as likely to have multiple sexual partners as their rural counterparts. The implications of these findings are discussed.